Warna Kontemporari Dalam Karya Seni - Roslan, Aimi Atikah; Syed Abu Bakar, Syed Alwi (Idealogy Journal, 2019)
The purpose of this study is to discuss on contemporary colours in artwork. Contemporary colours have developed a bridge between theory and practice, particularly in the production of works of art. While other studies have been conducted on colours solely, this one focuses on the relationship between artwork and contemporary colours. This teaches the reader that contemporary colours are an integral component of the world of painting and design art. The study of contemporary colours employs artwork to address the subject about the significance of modern colours. As a result, the significance of modern colours has become significant that it has evolved into a movement within the context of contemporary art. This writing is an attempt to convey information about colours using a common language. Keywords : Colour, contemporary